Mitigation of opioid off-target effects and identification of structural drivers of opioid receptor engagement for BACE-1 small molecule inhibitors. (24th July 2015) - Diaz, Dolores; Dambach, Donna; Siu, Michael; Hunt, Kevin; Thomas, Allen; Lyssikatos, Joseph; Liu, Xingrong; Lewin-Koh, Sock; McCray, Bobby; Ford, Kevin
Abstract: Application of safety lead optimization screening strategies during the early stage of drug discovery led to the identification of a series of CNS-active small molecule inhibitors with opioid off-target effects, as evidenced by potent agonistic activity in functional cell-based assays for mu (MOP), kappa (KOP) and delta (DOP) opioid receptors. The translation of these effects was confirmed in vivo with the following observations: hypoactivity and decreased fecal production in rats (characteristic of MOP agonism); increased urine production in rats (characteristic of KOP agonism); and decreased intestinal transit time in mice, which was partially blocked by the MOP antagonist naloxone, demonstrating that the in vivo effects were specific for MOP. Based on the confirmation of in vitro–in vivo translatability, an in vitro screening strategy was implemented that resulted in the identification of an optimized backup molecule, devoid of in vivo off-target opioid effects. In addition, in silico modeling by docking of the various molecules to the opioid receptors allowed the identification of the structural drivers of these off-target effects, which can be applied to future chemical-design criteria. Thus, implementation of the safety lead optimization strategy described in this article demonstrates the utility and impact of such approaches on risk mitigation and identification of lead small molecules with improved safety profiles.